The origins of Ethiopia's primary health care expansion: The politics of state building and health system strengthening. Issue 10 (10th November 2020) - Croke, Kevin
Abstract: Ethiopia's expansion of primary health care over the past 15 years has been hailed as a model in sub-Saharan Africa. A leader closely associated with the programme, Tedros Adhanom Gebreyesus, is now Director-General of the World Health Organization, and the global movement for expansion of primary health care often cites Ethiopia as a model. Starting in 2004, over 30 000 Health Extension Workers were trained and deployed in Ethiopia and over 2500 health centres and 15 000 village-level health posts were constructed. Ethiopia's reforms are widely attributed to strong leadership and 'political will', but underlying factors that enabled adoption of these policies and implementation at scale are rarely analysed. This article uses a political economy lens to identify factors that enabled Ethiopia to surmount the challenges that have caused the failure of similar primary health programmes in other developing countries. The decision to focus on primary health care was rooted in the ruling party's political strategy of prioritizing rural interests, which had enabled them to govern territory successfully as an insurgency. This wartime rural governance strategy included a primary healthcare programme, providing a model for the later national programme. After taking power, the ruling party created a centralized coalition of regional parties and prioritized extending state and party structures into rural areas. After a party split in 2001, Prime Minister Meles Zenawi consolidated power and implemented a 'developmental state' strategy. In the health sector, this included appointment of a series of dynamic Ministers of Health and the mobilization of significant resources for primary health care from donors. The ruling party's ideology also emphasized mass participation in development activities, which became a central feature of health programmes. Attempts to translate this model to different circumstances should consider the distinctive features of the Ethiopian case, including both the benefits and costs of these strategies.